Government environmental regulation and farmers' engagement in traditional folk practices: the mediating roles of ecological cognition and social norms - Wu, Qing; Feng, Jiaxiao; Liu, Xiaoshi; Huang, Yanli (Frontiers in Psychology, 2026)
IntroductionAs an important carrier of cultural identity and community cohesion in rural Chinese society, traditional folk activities often generate tensions with modern ecological protection goals due to their resource-intensive characteristics. This study takes the millennium-old “Firecracker Lion Dance” activity in Deqing County, Guangdong Province, as a research case to explore how government environmental regulation influences farmers' willingness to participate in the Sustainable Firecracker-Lion Dance Custom, with a particular focus on the mediating roles of social norms and ecological cognition.MethodsBased on 423 valid samples collected through fieldwork from 2022 to 2024, a structural equation model was constructed to systematically examine the differential regulatory pathways of incentive-based and coercive environmental regulation on farmers' participation in traditional folk practices, as well as the mediating roles of ecological cognition and social norms.ResultsThe results show that incentive-based regulation significantly enhances farmers' willingness to participate through motivational mechanisms (β = 0.229, p < 0.001), whereas coercive regulation shows no significant effect. Social norms exert significant positive effects on participation willingness (descriptive norms: β = 0.167, p < 0.001; injunctive norms: β = 0.238, p < 0.001), reflecting the behavioral constraints of group identity and opinion orientation in rural acquaintance societies. Meanwhile, ecological cognition significantly inhibits participation willingness (β = −0.210, p < 0.001) and exhibits a negative mediating effect in the coercive regulation path.ConclusionThis study provides deeper insight into that the effectiveness of environmental regulation in traditional folk practices depends less on regulatory intensity than on cultural compatibility. Social norms function as key cultural conduits that translate policy signals into behavioral acceptance, whereas ecological cognition may generate value tensions that constrain participation. The results of this study offer theoretical validation and practical significance for the integrated governance of culture and ecology within the paradigm of ecological civilization.